Evaluation of the application of MEP's guidelines for the Assessment of Action-Oriented Oral Comprehension and Oral Production Classwork in the listening and speaking class of group 9-1 in the current 2021 Blended Learning Context at Bilingual Experimental High School of Turrialba - Brenes Prendas, Jocelyne María 1997-; Monge Zelaya, Paula Isabel 1997-; Sanabria Mora, Esteban Antonio 1997-; Solano Mata, Yeniffer 1988- ([Turrialba, Cartago, Costa Rica], 2022)
Over the years, classwork has been considered as one of the key elements of class mediation and learning evaluation regardless of the teaching approach used in the Costa Rican public education system regulated by the Ministry of Public Education (from now on, "MEP"). In the communicative approach shaped in the 1980s and 1990s, for example, classwork was conceived as a task with an emphasis on content rather than form that aimed for students to be able to communicate in class using the content studied (MEP, 2017). More recently, this has been redefined with the incorporation of the Action-Oriented Approach (from now on AOA) as the basis for the newest English curriculum at MEP. According to MEP (2017), this new curriculum based on the AOA states that classwork activities must seek for students to practice the language in a meaningful way for successful real-life task completion. Classwork should favor the performance of tasks around moments, actions, and products that are vivid, defined, and concrete for the students. Therefore, former classwork activities such as grammar handouts, completion of book exercises, and other non-action-oriented tasks are no longer considered valid techniques to assess classwork. In other words, when performing tasks in a class mediated with this new AOA-based curriculum, "the learner is not speaking or writing for the teacher or pretending to speak or write to another person, but rather speaking or writing in a real-life context for a social purpose" (MEP, 2017, p. 26).
Seminario de graduación (licenciatura en enseñanza del inglés)--Universidad de Costa Rica. Sede del Atlántico. Recinto de Paraíso. Departamento Enseñanza del Inglés, 2022
Keywords: Liceo Experimental Bilingüe de Turrialba (Costa Rica); INGLES -- ENSEÑANZA SECUNDARIA -- TURRIALBA (CARTAGO, COSTA RICA) -- EVALUACION; PLANES DE ESTUDIO -- EVALUACION; ADQUISICION DE UNA SEGUNDA LENGUA -- ENSEÑANZA SECUNDARIA; COMUNICACION ORAL -- EVALUACION